2019
DOI: 10.1038/s41467-019-13640-1
|View full text |Cite|
|
Sign up to set email alerts
|

A VEGF receptor vaccine demonstrates preliminary efficacy in neurofibromatosis type 2

Abstract: The anti-VEGF antibody bevacizumab has shown efficacy for the treatment of neurofibromatosis type 2 (NF2). Theoretically, vascular endothelial growth factor receptors (VEGFRs)-specific cytotoxic T lymphocytes (CTLs) can kill both tumor vessel cells and tumor cells expressing VEGFRs. Here we show an exploratory clinical study of VEGFRs peptide vaccine in seven patients with progressive NF2-derived schwannomas. Hearing improves in 2/5 assessable patients (40%) as determined by international guidelines, with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…We have previously conducted exploratory clinical studies investigating VEGFRs peptide vaccination with and without multiple glioma oncoantigens in patients with recurrent high-grade gliomas [16,17]. Recently, VEGFRs peptide vaccine was used in patients with progressive neurofibromatosis type 2 (NF2) [18]. In the study, the number of Foxp3-positive regulatory T cells (Tregs) decreased after the vaccination, suggesting that the CTLs induced by the vaccination can directly kill a wide variety of cells associated with tumor growth, including tumor vessels, tumor cells, and Tregs expressing VEGFR1 and/or VEGFR2.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously conducted exploratory clinical studies investigating VEGFRs peptide vaccination with and without multiple glioma oncoantigens in patients with recurrent high-grade gliomas [16,17]. Recently, VEGFRs peptide vaccine was used in patients with progressive neurofibromatosis type 2 (NF2) [18]. In the study, the number of Foxp3-positive regulatory T cells (Tregs) decreased after the vaccination, suggesting that the CTLs induced by the vaccination can directly kill a wide variety of cells associated with tumor growth, including tumor vessels, tumor cells, and Tregs expressing VEGFR1 and/or VEGFR2.…”
Section: Introductionmentioning
confidence: 99%
“…Our exploratory clinical trial also demonstrated that VEGFRs peptide vaccination showed hearing improvement and tumor volume reduction in NF2 patients. There were no severe adverse events related to the vaccine [ 15 ]. Recently, we initiated another clinical trial using a VEGFRs peptide vaccine for recurrent, progressive, and refractory benign brain tumors (hemangiopericytoma, hemangioblastoma, meningioma, chordoma, and ependymoma).…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients had a potentially relevant past medical history, such as vasculopathy, in the Vac and Vac + Bev groups. Data from CTL induction were also collected, which were evaluated by the contract research organizations “OncoTherapy Science, Inc. (Kanagawa, Japan) and “Cancer Precision Medicine, Inc. (Kanagawa, Japan)””, as previously described [ 15 , 32 ]. To assess the relationship between the clinical information and the adverse events in the Vac + Bev group, and to evaluate the adverse event rate among these groups, the chi-squared test was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations